Agronomical traits performance and variability of the SSD F4 mungbean population - SURJONO HADI SUTJAHJO; NUR KHOLISOH; HESTI MAULIDA; SITI MARWIYAH; DESTA WIRNAS; EDIZON JAMBORMIAS (Jurnal Natural, 2023)
Genetic variability is critical in order to create candidates for new superior varieties. This research objective was to evaluate the performance and variability of agronomical traits on the mungbean SSD F4 V422H/129 population. The research was conducted at IPB University, Bogor, from March to June 2021. The SSD F4 VR422H/129 population (378 genotypes with single plant as a representative of one genotype) and five check varieties were evaluated. The treatments were arranged in augmented design for RCBD in three replications. For agronomical traits, every F4 plant and 10 sample plants for each check variety were observed. Statistical analysis includes mean, frequency-distribution, heritability, genetic variability, correlation. The days to flowering, days to harvesting, generative periods, plant height on F4 V422H/129 were not significantly different from Vima 5, while total pod number, total pod weight, total seed weight, pod length were significantly higher. The agronomical traits were affected by genetic factors (heritability 0.71-0.99%), except for days to harvest. Based on the high genetic variability (CGV 0.62-0.64%), it was possible to select of total pod weight, total seed weight, or pod length in the next generation V422H/129. The total seed weight had a significant positive correlation with total pod weight and pod length.